How to leverage on the Portuguese luxury consumers to increase the luxury consumption in Portugal? - Pinto, Catarina Rodrigues Ferreira (2019)
This dissertation aims to investigate the Portuguese Luxury Consumer’s consumption habits in Portugal, in order to understand how Portugal can capitalize on these consumers to further develop the overall luxury consumption in the country. To achieve this goal, we started by exploring the concept of luxury, presenting the main global luxury trends and analysing the luxury consumption in Portugal, using both qualitative and quantitative techniques. This investigation shows that Portuguese luxury consumers are influenced by store service, price and promotion, purchase both luxury goods and experiences, browse online before going to stores and, overall, seem to be aligned with the rest of the Western World’s luxury consumers.